RTL hardware design using VHDL : coding for efficiency, portability, and scalability - Chu, Pong P., 1959- (Wiley-Interscience, 2006)
The skills and guidance needed to master RTL hardware designThis book teaches readers how to systematically design efficient, portable, and scalable Register Transfer Level (RTL) digital circuits using the VHDL hardware description language and synthesis software.